Creation of potential gene cassette for recombinant protein expression in green microalgal system - Kadkhodaei, Saeid (2014)
Development of efficient strategies and reliable systems for production of recombinant proteins in high quality and quantity to reach the market are gaining more attraction. On the economic side, improvement of the efficiency and cost effectiveness of production process is highly required to be commercially viable. Although many strategies have been theoretically established to increase the level of gene expression in different specific host systems, it is needed to be practically applied. Due to the lack of enough information for expression of recombinant proteins in microalgal systems, the present study aimed at creation of a gene cassette utilizing both upstream (bioinformatics and computational analysis, genetic engineering and molecular biology) and downstream factors (bioprocess engineering) which may have critical roles in gene expression with the emphasis on two microalgae species, Dunaliella salina and Chlamydomonas reinhardtii. As the first step in evaluating the feasibility of molecular farming in microalgae, some of the important upstream factors including matrix attachment regions (MARs), translation initiation sites, signal peptides and gene optimization parameters were studied. An artificial universal MAR sequence was designed and developed considering the MAR specific rules and motifs. To explore the specific translation initiation site, all mRNA sequences in the microalgae D. salina were screened among which the nonredundant mRNAs were selected for bioinformatics analysis. A consensus sequence was finally created to be used in the specific expression vector. For the secretion systems in microalgae D. salina, a screening procedure was carried out to find the specific signal peptides using bioinformatics and in silico tools in DNA, RNA and protein databases. The predicted sequences were then selected for further characterizations and the highest scored predicted signal was embedded in the secretion series of expression vectors. For optimization of the coding sequences, the most important parameters such as the host codon preference, RNA secondary structure, GC and CpG dinucleotides content were taken into consideration. The final expression cassette containing all of the required elements including MAR, signal peptide, translation initiation site, KDEL retention signal, His 6x purification tag, V5 epitope and protease cleavage site was integrated into 25 expression vectors (25 vectors containing different elements). To develop a proprietary series of microalgae specific expression vectors, nine fragments containing the Gateway recombination cassette, optimized genes of interest (2), promoters (2), 5’- UTR, interon, 3’-UTR (2), MARs (2) and pUC18 backbone were amplified using the most high fidelity enzyme available (KAPA). The fragments were successfully assembled in a single recombination reaction through the novel multiple overlap extension PCR (MOE-PCR) technique developed in this study. To assess the efficient transformation techniques for microalgae, three different methods (electroporation, glass beads and PEG-mediated) were used to transform one Dunaliella and three Chlamydomonas strains using the developed expression vectors. Glass bead method with 10 s agitation time, 4% PEG and 300 ng/μL plasmid DNA, as an efficient and simple technique showed the best results despite a drop in viable cells. The use of specific expression vectors resulted in more number and more stable transformants comparing a commercially available vector (pCAMBIA-3301) without the abovementioned optimized elements. The expression cassette containing optimized genetic elements could be delivered into microalgae cells and confer the resistance to the transformants for at least 3 months. For the downstream processes, the culture condition of D. salina was optimized to be used for future studies of the transformants. An experiment was conducted based on response surface methodology (RSM) to realize the reaction of microalgae to different phototrophic conditions including heterotrophic, mixotrophic and phototrophic. It was observed that the higher the amount of supplemented glucose up to 15 g/L, the more glucose utilization, biomass concentration and consequently protein content obtain. The results demonstrated superiority of mixotrophic conditions in constant light in improving the growth of microalgae. This study demonstrated that the upstream factors such as MARs, translation initiation sites and gene optimization along with the optimized transformation systems and downstream processes, could be a potential procedure to be efficiently used in overexpression of recombinant protein production using microalgae as the expression platform. Considering the close relatedness of the studied microalgae and other close species, the proprietary vector series could be generally used in genetic engineering of at least green microalgae.